2022
DOI: 10.1371/journal.pone.0260018
|View full text |Cite
|
Sign up to set email alerts
|

ABO blood type and clinical characteristics of patients with ulcerative colitis: A hospital-based study in central Taiwan

Abstract: Background The variations in ABO blood groups are reported to be associated with multiple disorders, including ulcerative colitis (UC). We aimed to investigate the distribution of ABO blood groups in UC patients and explore its impact on disease severity. Methods We retrospectively collected 129 UC patients diagnosed at our hospital between January 2000 and November 2019. Clinical characteristics, ABO blood groups, and operation rates were analyzed. Results The mean diagnostic age of patients was 38.97 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…In Table 2 there were also many research studies that discussed and explored the relationship between blood grouping and autoimmune diseases there was no significant relation between blood types and 2021) all these researchers explained that there was no relation between autoimmune diseases and blood types (1,20,21). Also, a research study by Lai et al (2022) explaining ulcerative colitis showed no association between blood type and ulcerative colitis that type A has high baseline hemoglobin and type O has higher baseline ESR levels [13,14]. Related to psoriatic arthritis cross-sectional and clinical and laboratory research done the result showed that there was no significant relation between psoriatic arthritis and blood grouping [15,16].…”
Section: Resultsmentioning
confidence: 99%
“…In Table 2 there were also many research studies that discussed and explored the relationship between blood grouping and autoimmune diseases there was no significant relation between blood types and 2021) all these researchers explained that there was no relation between autoimmune diseases and blood types (1,20,21). Also, a research study by Lai et al (2022) explaining ulcerative colitis showed no association between blood type and ulcerative colitis that type A has high baseline hemoglobin and type O has higher baseline ESR levels [13,14]. Related to psoriatic arthritis cross-sectional and clinical and laboratory research done the result showed that there was no significant relation between psoriatic arthritis and blood grouping [15,16].…”
Section: Resultsmentioning
confidence: 99%
“…A study from Taiwan involving 129 UC patients found that there was no association between ABO blood type and UC, even though blood type A was more prevalent. Patients with blood type O had higher erythrocyte sedimentation rate levels, whereas those with blood type A had higher hemoglobin levels [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, the sample size may have been too small to accurately assess the relationship between ABO blood type and clinical outcomes. Considering the poor clinical outcomes (operation) in O blood type (6.98%) and non-O blood type (4.65%) [ 12 ], and assuming a detection rate of 75% (two-tailed test, p < 0.05), the calculated sample size was 1,400. Third, the cohort had a high rate of exclusion due to missing data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these previous studies show an increased risk of cumulated radiation exposure among IBD patients [ 7 , 8 , 9 , 10 , 11 ], no previous report addressed this issue among the Taiwanese population. As the incidence and prevalence of IBD are increasing in Taiwan [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ], it is essential to understand the pattern of radiation exposure in this growing population. Therefore, we conducted this study to estimate the radiation exposure and analyze possible risk factors associated with radiation exposure among Taiwanese IBD patients.…”
Section: Introductionmentioning
confidence: 99%